Capillary malformation/arteriovenous malformation associated with limb hypertrophy. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2022)
The child of the actual presentation lends itself very well to discussing the relationships between port-wine stain (PWS), capillary malformation/arteriovenous malformation syndrome (CM/AVM), Klippel-Trénaunay syndrome (K-T) and Parkes Weber syndrome (PW). The child has multiple red spots that thanks to family and personal history and distribution are diagnosable as CM/AVM. The history of family members with CM/AVM, the presence of acquired similar lesions and above all the random distribution of the lesions makes it possible to exclude PWS. (...)